Defect induced stress in ion irradiated nanocrystalline Ge2Sb2Te5 - Marcos, Veronica Lopez; Asemann, Patricia; Schrempel, Frank; Ronning, Carsten; Wendler, Elke (Materials Letters, 2022)
Nanocrystalline Ge2Sb2Te5 (GST) was irradiated with Au (700 keV) or Si (150 keV, 700 keV) ions over a wide range of ion fluences. Measuring the radius of curvature of the samples during irradiation revealed significant changes of the depth-integrated stress within the irradiated GST layer. In combination with Raman spectroscopy, the first increase of stress is attributed to the formation of point defects. This stress increase diminishes most probably by changes in the microstructure of defects with increasing ion fluence. Finally, the successive amorphisation of GST causes a second increase of stress within the irradiated layer during proceeding irradiation due to the reduction of density.
CRIS-Team Scopus Importer:2023-04-20
Keywords: GST; Ion irradiation; Layer stress; Nanocrystalline materials; Radiation damage; Raman spectroscopy